Decision conflict and the decision support needs of HIV PrEP-eligible Black patients in Toronto regarding the adoption of PrEP for HIV prevention. (January 2022) - Ajiboye, Wale; Nelson, LaRon; Odhiambo, Apondi; Yusuf, Abban; Djiadeu, Pascal; Turner, De Anne; Abubakari, M'Rabiu; Pedersen, Cheryl; Brown, Rebecca; Ni, Zhao; Guillaume, Genevieve; Lofters, Aisha; et al.
Objectives: This study examined factors contributing to decision conflict and the decision support needs of PrEP-eligible Black patients.Methods: The Ottawa Decision Support Framework (ODSF) was used to guide the development of a key informant guide used for qualitative data collection. Black patients assessed by healthcare providers as meeting the basic criteria for starting PrEP were recruited through the St. Michael's Hospital Academic Family Health Team and clinical and community agencies in Toronto. Participants were interviewed by trained research staff. Qualitative content analysis was guided by the ODSF, and analysis was done using the Nvivo.Results: Four women and twenty-five men (both heterosexual and men who have sex with men) were interviewed. Participants reported having difficulty in decision making regarding adoption of PrEP. The main reasons for decision-conflict regading PrEP adoption were: lack of adequate information about PrEP, concerns about the side effects of PrEP, inability to ascertain the benefits or risk of taking PrEP, provider's lack of adequate time for interaction during clinical consultation, and perceived pressure from healthcare provider. Participants identified detailed information about PrEP, and being able to clarify how their personal values align with the benefits and drawbacks of PrEP as their decision support needs.Conclusion: Many PrEP-eligible Black patients who are prescribed PrEP have decision conflict which often causes delay in decision making and sometimes rejection of PrEP. Healthcare providers should offer decision support to Black patients who are being asked to consider PrEP for HIV prevention.